2019
DOI: 10.1111/jocn.15027
|View full text |Cite
|
Sign up to set email alerts
|

Midwives' use of best available evidence in practice: An integrative review

Abstract: Aims and objectives To synthesise international research that relates to midwives' use of best available evidence in practice settings and identify key issues relating to the translation of latest evidence into everyday maternity care. Background Midwifery is a research‐informed profession. However, a gap persists in the translation of best available evidence into practice settings, compromising gold standard maternity care and delaying the translation of new knowledge into everyday practice. Design A five‐ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Since the interviews were of a relatively long length and data were content-rich these issues did not appear to have negatively influenced the findings. In-depth interviews can be considered appropriate when wanting to improve or implement patient- or women-informed evidence-based maternity care 30 . To be noted, the sample size only represents women having an uncomplicated childbirth and mainly including multiparous women.…”
Section: Discussionmentioning
confidence: 99%
“…Since the interviews were of a relatively long length and data were content-rich these issues did not appear to have negatively influenced the findings. In-depth interviews can be considered appropriate when wanting to improve or implement patient- or women-informed evidence-based maternity care 30 . To be noted, the sample size only represents women having an uncomplicated childbirth and mainly including multiparous women.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research would be interesting to deepen this relation, and the other factors we identified in relation to the implementation of EBP, so we know how to reach every midwife (irrespective of the demographic background) to implement EBP guidelines. Understanding midwives’ use of best available evidence in practice will direct efforts towards developing mechanisms that facilitate the timely uptake of the latest evidence by all maternity care providers working in clinical settings 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based practice (EBP), ”the conscientious, explicit, and judicious use of current best evidence in making decisions about the care of individual patients” [ 112 ] (p.71) positively impacts patient outcomes in nursing and midwifery, reduces healthcare costs and empowers nurses and midwives, resulting in the WHO Regional Office in Europe urging its Member States to encourage and develop EBP culture in nursing and midwifery [ 113 ]. An integrative review found that although EBP in midwifery is valued, implementation is still lacking [ 114 ]. Similarly, Lai et al [ 115 ] found that nursing and allied health practitioners in several Malaysian hospitals reported less favourable attitudes towards EBP, which could possibly be due to the low confidence attributed to their diploma qualification level.…”
Section: Discussionmentioning
confidence: 99%